A Cross-Sectional Study of Elite Adult Irish Dancers: Biopsychosocial Traits, Pain, and Injury. Issue 1 (March 2015) - Cahalan, Roisin; Purtill, Helen; O'Sullivan, Peter; O'Sullivan, Kieran
Despite its growing popularity, scant research exists concerning musculoskeletal pain and injury in Irish dancing (ID). This study aimed to record the biopsychosocial characteristics of elite adult Irish dancers and to investigate potential relationships between these characteristics and musculoskeletal pain and injury. One hundred and four professional Irish dancers, elite competitive Irish dancers, and dancers in full time education studying ID completed a questionnaire providing data on dance and activity levels, physical and psychological health, and pain and injury history. Of these subjects, 84 underwent 1. a physical screening of lower limb flexibility, which involved balance and endurance; 2. a number of functional tests; and 3. anthropometric, biomechanical, and anatomical assessments. Subjects were divided into "significantly injured (SI)" and "not significantly injured (NSI)" categories based on the severity and impact of self-reported pain and injury. Thirty-three (31.7%) subjects were classified as SI and 71 (68.3%) as NSI. The factors significantly associated with being SI were female sex (p = 0.036), higher number of subjective general health (p = 0.001) and psychological (p = 0.036) complaints, low mood (p = 0.01), heightened catastrophizing (p = 0.047), and failure always to complete a warm-up (p = 0.006). A self-reported injury rate of 76.9% over the previous 5 years was reported. The mean number of injuries sustained to all body parts over the previous 5 years was 1.49, with a mean of 126.1 days lost annually to injury. Foot and ankle injuries were most prevalent. It was concluded that there is a significant level of musculoskeletal pain and injury in elite adult ID. A complex combination of biopsychosocial factors appears to be associated with pain and injury.